Research development units in teaching hospitals: performance and strategies for improvements - Afsoon Aeenparast; Kazem Zendehdel; Faranak Farzadi; Farzaneh Maftoon; Telma Zahirian moghadam; Hamed Zandian (Payesh, 2014)
Objective (s): to evaluate research development units in teaching hospitals. Methods: This was a qualitative study that was conducted at national level in Iran. We used standardize open–ended interviews and focus group discussions for data collection. Experts were selected according to their experiences; activities and cooperation levels with ministry of health and research development units. Results: In all four main themes emerged from analysis: i) necessity of establishing clinical research development units in teaching hospitals, ii) units’ limitations, iii) organizational structure and financing, iv) strategies for improving these units. Conclusion: The findings indicated areas that need improvements including providing appropriate resources for these units.